2016
DOI: 10.1016/j.ijporl.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up in newborn hearing screening – A systematic review

Abstract: This review is a novel attempt to explore the LTF among NHS studies, reasons for LTF and strategies to reduce LTF. This review can act as a basis for planning and execution of effective NHS programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 62 publications
2
53
2
5
Order By: Relevance
“…In 37.9% of the newborns, an intervention by the screening center was conducted to assure the control of a failed screening or control test. Other countries or regions without a tracking system have to deal with lost-to-follow-up rates of up to 60% [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 37.9% of the newborns, an intervention by the screening center was conducted to assure the control of a failed screening or control test. Other countries or regions without a tracking system have to deal with lost-to-follow-up rates of up to 60% [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systemic review of 53 articles, the average dropout rate which is loss to follow up after screening test was 20% in single-center studies and 21% in multiple-center studies. Reasons of a high dropout rate were the educational disparity, lack of adequate knowledge of parents, and lack of an adequate data management system which is the most important strategy to decrease PLOS ONE the dropout rates during follow-up period after screening [21]. If we consider infants who are not included in the documented diagnostic ABR conducting rate, the number of hearingimpaired infants may be higher than reported data.…”
Section: Plos Onementioning
confidence: 98%
“…22,3638 A recent systematic review involving reports from multiple countries assessed barriers to follow-up after newborn hearing screening and found that educational disparities, travel distance, work constraints, unfavorable attitudes, and competing healthcare needs were the primary reasons for non-adherence. 39 Families of children with hearing loss report that they lack confidence and resources needed for healthcare decision-making for their child. 40 Many parents lack role models who have been through the complex process of hearing loss diagnosis and intervention 41 because more than 90% of deaf children have hearing parents.…”
Section: Barriers To Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%
“…Proposed methods for improving loss to follow-up for diagnostic testing in many countries throughout the world include the use of a database management system, increased parental education, telephone reminders, multidisciplinary team management, and flexibility in appointment scheduling. 39 There are also advances in screening for causes of pediatric hearing loss, such as cCMV. Screening for cCMV is typically completed within the first 3 weeks after birth and evidence of cCMV positivity can promote timely infant hearing testing after screening.…”
Section: Innovations In Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%